Sistem Pendukung Keputusan Pemilihan Pastor Terbaik Menerapkan Metode Vikor - Jafelius Gulo (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Medan Archdiocese is a metropolitan ecclesiastical province in unity with two suffragan dioceses nearby, namely Padang Diocese and Sibolga Diocese. Pastor is the name for a priest who leads a parish. The pastor is obliged to celebrate Mass for his parishioners, has the right to be the main witness in confirming a marriage, is obliged to fill in the records of baptisms, confirmations, marriages and deaths. The Second Vatican Council said that the head pastor is the true pastor of the people in which he performs pastorial care. The problem in selecting pastors so far is that by making bishops confused to choose pastors in Medan dioceses it is considered very ineffective and efficient due to the confusion of bishops in choosing pastors to fulfill the guidance of the current election process. efficiency is due to the fact that many bishops do not vote. to overcome this problem, the VIKOR Method is applied to make decisions. Aiming to get alternative ranking results that are close to the ideal solution by proposing a compromise solution, by implementing decision making, the results obtained will be more optimal, in using computerized decision support systems besides being able to speed up the decision-making process it can also help process data more accurately and precisely To use.